Cardiogenic Shock Among Yemeni Patients Presented With Acute Coronary Syndrome (ACS). Data From Gulf Registry of Acute Coronary Events Phase (Gulf Race I) - Munibari, A-Nasser; Almotarreb, Ahmed; Alansi, Ahmed K.; Alsaghir, Nora; Abodadi, Hanaa; Hamoud, Abdo; Alawlaki , Motae; Mihdhar , Salim (Thamar University Journal of Natural & Applied Sciences, 2023)
Introductions & Aims: Acute Coronary Syndrome (ACS) and its magnitudes is one of the most common cardiac diseases world-wide. Yet in Yemen; GULF RACE I data are the first nation- wide information that highlight the magnitude of this problem. Cardiogenic shock is a miserable complication of ACS. Pointing out this problem among Yemeni with ACS, its prognostic importance and impact in patients outcomes is a major aim of this study.Methods and Patients: Yemen data arm was a part from the GULF RACE I, which is a prospective, multinational, multicentres survey of consecutive patients hospitalized with the final diagnosis of ACS in six Arabian Peninsula/Gulf countries over a period of six month. Yemeni patients were 1054 patients included from 20 major hospitals all over the country with ACS including cases of ST Elevation Acute Myocardial Infarction (STEMI), non ST Elevation Acute Myocardial Infarction (NSTEMI), newly developed Left Bundle Branch Block (LBBB) and unstable angina pectoris (UA). Patients with Acute Heart Failure (AHF) and presented with cardiogenic shock were pointed out. The end point of this study was all causes of in-hospital mortality.Results: Out of 1054 hospitalized with ACS, 181 patients (17.3%) had AHF on presenting to the hospital or during hospitalization itself. Out of those patients with AHF there were 74 patients who developed Cardiogenic Shock. They were relatively older 64.7±9.7 (SD) years (P <0.001) with male predominance (63.5%). In spite of Anterior/Anteriolateral STEMI was a common feature of presentation (70.2%), echocardiographic feature were moreconsistent with cardiogenic shock , Left Ventricular Ejection Fraction (LVEF) was (36.5% Vs 51% P <0.001). Those patients were in co-morbid condition more than the rest of the group of ACS & evidently were less treated utilizing evidence based treatment. Cardiogenic shock was linked to higher in hospital mortality (66.2% Vs 4.8% with P < 0.001).Conclusion: Yemeni patients with acute coronary syndrome complicated with cardiogenic shock had more worse prognosis regarding in-hospital morbidity and mortality.